The healthy diet effect with project based learning animation on student concentration and learning outcomes - Mukra, Rizal; Ulina Silalahi, Dewi Ratna Sari; Sembiring, Safira Salsabilla Ayudia Balqis; Ritonga, Viony Azzahra; Putri, Dwi Fadhillah; Putri, Allysha Dinda (JPBIO (Jurnal Pendidikan Biologi), 2024)
A healthy diet affects students' learning concentration to obtain optimal results. If a child eats healthy food, the food is certainly good, good food is not necessarily healthy food. The purpose of the study was to determine the effect of a healthy diet on concentration and learning outcomes assisted by interactive learning videos based on Project Learning at SMA Tamansiswa Binjai. This research was conducted in September 2024. The method used in this research is a quasi-experiment research design with the form of a pretest and posttest control group design. The research population was the XI MIPA class of Tamansiswa Binjai. The Sample was taken using a purposive sampling technique and obtained XI MIPA 1 as the experimental class. The research instruments used were tests and questionnaires. The data analysis technique used a One-way ANOVA test. Based on data analysis, it can be concluded there is an effect of a learning concentration with a learning outcome in class MIPA 1 SMA Tamansiswa Binjai.